HIV infection and Syphilis among people a ttending a STD clinic in Brazil - Miranda, Angélica E.; Monteiro, Rafael B.; Prado, Bruno C.; Serafim, Rafael R.; Soares, Rafael A. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Objectives: To identify the epidemiological profile and to determine the seroprevalence of HIV infection and syphilis among STDs clinic patients. Methods: Cross-sectional study was conducted from March to June 2002. They were interviewed using a structured questionnaire and a blood sample was collected for testing HIV and syphilis. They were included after answer the consent inform. Results: A total of 427 first time patients were included. The mean age was 28.8 years old (SDI 10.3), mean education was 8.4 years of schooling (SD 3.0) and the mean age of the first sexual intercourse was 15.9 years old (SD 2.8). The prevalence rates were HIV infection 7.0 % (Cl 95%(5.8-8.3)| and syphilis 11.7% [Cl 95% 10.1-13.3)]. Only 61 (14.3%) reported frequent condom use. The risk factors accessed were 91.3% heterosexuals; 4.4 bisexuals and 4,3 homosexuals. Previous STDs 29.3%, drug abuse 9.6% and history of transfusion 4.7%. There were statistical association among HIV infection and syphilis |OR=3.07 (95% IC 1.29-7.33)]. HIV infection and drug abuse [OR=4.88 (95%IC 2.07-1 l.55)J, syphilis and drug abuse |OR=3.26 (95%IC 1.54-7.01)] and syphilis and previous STDs (OR=4.04 (95%IC 2.20- 7.42)].Conclusion: Data show a high prevalence of the analyzed infections and asking for new studies to evaluated the situation. They are important to identify the profile of STD clinic patient and to give directions to implementing prevention and assistance strategies.